Analisis Bentuk Bahasa Gaul Dan Bahasa Tidak Baku Pada Lirik Lagu Viral Tiktok “Stecu-Stecu” - Indrawati; Khavida Inzania Nelly Agustina; Khilya Fuadina; Muhammad Rhois; Laila Tri Lestari; Miftahul Huda (Universitas Muhammadiyah Surabaya, 2026)
This study aims to describe the forms of slang and non-standard language in the lyrics of the TikTok song